Growth And Production Of Some Local Grass Species on Various Long Of Defoliation - A.N., Muhammady; Trisnadewi, A. A. A. S; Suranjaya, I G. (Jurnal Peternakan Tropika; Vol 6 No 3 (2018), 2018)
This study aims to obtain information about the influence of the length of defoliation on growth and grass production. The study was carried out in the green house of the Faculty of Animal Science, Udayana University for 10 weeks. The design used was a completely randomized design (CRD) pattern of split plot, main plot / species of grass and sub plot / sub plot long defoliation with replications four times so that there were 48 experimental units. The grass used is three species of local grass were Axonopuss compressus , Stenotaphrum sucundatum and Paspalum conjugatum . With treatment D1 = 5 cm defoliation treatment, D2 = 10 cm defoliation, D3 = 15 cm defoliation and D4 = 20 cm defoliation. The variables observed were plant length, number of leaves, number of tillers, leaf dry weight, stem dry weight, root dry weight, total dry weight of leaves, ratio of leaf dry weight to stem dry weight, ratio of total forage dry weight to root dry weight and broad leaves per pot. The results showed that plant species were significantly different in plant length variables, number of tillers, leaf dry weight, stem dry weight, total dry weight of forage and leaf area. The results of the defoliation length were significantly different in the plant length variable, number of leaves and dry weight of the stem. Based on the results of the study it can be concluded that D4 defoliation = 20 cm tends to give a positive response and Paspalum conjugatum grass gives the highest growth and production response and there is no interaction between the length of defoliation and the type of grass.  Key words: local grass, defoliation, growth, production